O clima de Santa Cruz do Sul - RS e a percepção climática da população urbana - Ruoso, Diamar (2007)
This thesis was an attempt to evaluate the degree of the individuals' climatic perception in the urban area of Santa Cruz do Sul RS with the purpose of collaborating with the development of the studies of environmental perception. The work was divided into two main parts: the climatological approach and the approach of the climatic perception. In the climatological approach, data of the Meteorological Station of the University of Santa Cruz do Sul (UNISC), from 2004 and 2006, were used. In the analyses, such years were considered atypical. Therefore, climatic data of the Climatological Normal of INMET (National Institute of Meteorology) and IPAGRO (Institute of Agricultural Researches) were collected for the construction of graphs of temperature frequency and precipitation for comparison of local answers to the regional atmospheric circulation of Santa Cruz do Sul and Santa Maria, in order to verify if the meteorological data of Santa Maria could be used. Proven the climatic similarity between both municipal districts, data of the Meteorological Station of Santa Maria in terms of temperature and precipitation were collected considering a period of 36 years (1970 - 2005) with which analyses through frequency graphs were carried out, reaching the habitual standard year 1992. Rhythmic analysis based on Monteiro (1976) taking into account February, 2006 was also carried out. During this month, interviews were accomplished through forms in order to investigate the climatic perception of citizens in Santa Cruz do Sul, according to approach proposed by Sartori (2000). Nine types of weather in February, 2006 were identified, and several perceptive answers from 128 inhabitants were obtained. People answered personal questions and, in their opinion, what weather and climate were and what types of weather they liked the most; they also talked about the genesis of the climate and the influence of the media in the official forecast of the weather, besides popular sayings or personal observations to foresee rain, droughts, among other atmospheric phenomena. All the answers presented by the population prove the great and unanswerable interaction man-nature, which results in the perception and environmental cognition. Among other results, the nine types of weather identified are part of the weathers associated with extra-tropical systems and disturbed currents. The urban population of Santa Cruz do Sul, through the application of the interview forms, showed, in general, relevant perceptive answers. The citizens understand well what weather is, but they can't distinguish between weather and climate. Many of the answers given by the individuals are influenced by the media. Interesting that most of the interviewees mentioned and detached the importance of signs of the nature and psychophysiological reactions like, for instance, rain indication and/or good weather/drought. That is because many individuals are from rural area, and the ones who have always lived in the city had a tendency and are interested in observing the weather conditions. This way, it became clear the environmental and climatic perception that was looked for, rescuing the popular knowledge, very rich in experiences in the lived space.